Strategies of self-presentation in the business meetings and negotiation - Mažeikienė, Aistė; Peleckis, Kęstutis (Business: Theory and Practice, 2009)
The paper aims to analyse the phenomenon of self-presentation in business surroundings - a behavioural mode by which it is strived under public business surroundings to achieve an agreement and to avoid repudiating orienting to universally adapted norms and other people’s expectations. In the article the main strategies of self-presentation are described, which are used in business meetings and negotiation situations. The motivation of self-presentation develops under public situations, because it is characteristic of a person to take an interest in people how they consider and evaluate other people. Therefore, a person realising himself as a social object, tries to perceive and see himself as such who can be seen by others, and, representing himself correspondingly in business meetings and negotiation, tries to show himself to be accepted and evaluated, and/or in such a way that when regulating other people’s impressions on himself, when getting particular results in business, he or she could confirm his (her) own identity. The paper enlarges the understanding of self-presentation, which influences both person’s identity and his state shaping in business interaction.Prisistatymo strategijos dalykiniuose verslo pokalbiuose ir deryboseSantrauka. Straipsnyje analizuojamas prisistatymo reiškinys dalykiniu požiūriu – kaip elgsena, kuria viešoje verslo aplinkoje siekiama gauti aplinkinių pritarimą savo pozicijai ir išvengti atmetimo, orientuojantis į visuotinai priimtas normas ir kitų žmonių lūkesčius. išskiriamos svarbiausios dalykinių pokalbių ir derybų metu naudojamos prisistatymo strategijos. Prisistatymo motyvacija kyla viešose verslo situacijose, nes žmogui būdingas domėjimasis ir rūpinimasis tuo, kaip jį suvokia ir vertina kiti žmonės. Todėl asmuo, įsąmonindamas save kaip socialinį objektą, bando pateikti save taip, kad būtų priimamas ir vertinamas dalykinių susitikimų, pokalbių ir derybų metu, ir taip, kad, valdydamas kitų žmonių įspūdžius apie save, patvirtintų savo tapatybę pačiam sau. Šiame darbe išplečiama samprata prisistatymo, darančio įtaką tiek paties asmens identiškumo, tiek jo visuomeninio ir profesinio statuso formavimui bei suteikiančio kryptį tarpasmeninei sąveikai dalykinio bendravimo metu.Reikšminiai žodžiai: prisistatymas, prisistatymo strategija, įspūdžio kūrimas, asmens tapatybė, kitų žmonių reagavimo įsisąmoninimas, savęs stebėjimas.First Published Online: 10 Dec 2009